Knowledge Management Peculiarities in MSMEs - Arum Arupi Kusnindar; Ambya Ambya; Ayi Ahadiat; Dewi Mariam Widiniarsih (Sean Institute, 2026)
Knowledge Management (KM) in Micro, Small and Medium enterprise (MSMEs) have unique and different process with large business in running the business and decision making process. These different coming from how the company manage the knowledge. MSMEs use to have more informal culture and structure compared to large organization. These informal knowledge ussuly owned by the founder. This type on knowledge known as tacit knowledge. MSMEs often rely heavily on the expertise of their expertise and experiences if their employee or founder who possess tacit knowledge. So, Capturing and sharing tacit knowledge becomes crucial for business success. Enabling knowledge sharing if very necessary for long term MSMES resilience. The knowledge sharing process may happen organically through daily interaction rahther than formalized process. MSMEs also have limited resources include financial, human resources. This can impact the ability to invest in sophisticated KM System or dedicated personnel to manage knowledge. These knowledge management peculiarities can provide valuable insights and best pratices, implement Strategy such as low cost tools, and building networking. Emphasizing a culture of continuous learning and encouraging employee to document and share their expertise can alsi contribute to effective knowledge management in MSMEs.